LIBERAL IDEOLOGY: AN OUTLINE OF ORTHODOX CRITICISM - Іщук, Н. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article deals with the legitimization perspective of the social liberal paradigm by the contemporary orthodoxy.